Use of artificial intelligence and virtual reality within clinical simulation for nursing pain education: A scoping review. (February 2021) - Harmon, Joanne; Pitt, Victoria; Summons, Peter; Inder, Kerry J.
Abstract: Objectives: To explore and map the evidence for virtual reality and artificial intelligence in simulation for the provision of pain education for pre and post registration nurses. Design: A scoping review of published and unpublished research from 2009 to 2019. Data sources: Nine electronic databases and hand-searching of reference lists. Review methods: Studies were included if virtual reality or artificial intelligence interventions were used for education on pain care provision in nursing. Data were extracted and charted using an extraction tool and themes were explored using narrative analysis. Results: The review process resulted in the inclusion of four published studies. All studies used mixed methods and used artificial intelligence within clinical simulations as an intervention. No studies using virtual reality for pain education met the inclusion criteria. Participants of three studies were undergraduate nursing students in universities and participants in the fourth study were registered nurses within a hospital. Outcomes measured were user acceptance of the technology and feasibility in all studies. The context was hospital located and focused on acute pain episodes, with one exception being sickle cell pain. Three studies had adult patients and the other pediatric patients. The exclusion of input from a patient perspective was notable, as was a lack of interdisciplinary involvement. Conclusion: Nurses are integral to the assessment and management of pain in many care settings requiring comprehensive communication and clinical skills. There is a paucity of research on the use of virtual reality or artificial intelligence in pain education for nurses. Current studies are preliminary in nature and/or pilot studies. Further empirical research, with robust design is required to inform nursing education, practice, and policy, thereby supporting the advancement of nursing pain education.